Comparison between Kriging and Lognormal Kriging for Sulfur Data - Najla Sedek Yehya, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper deals with the spatial estimation to be optimal estimate when the data have a normal distribution. Ordinary kriging technique used in this research and lognormal kriging after take logarithm of original data. Variogram function uses in this research to obtain the best model of covariance function. The objective of this research is to assess the resistance of ordinary kriging and lognormal kriging to outliers. The data adopted of this paper from hydrogeological hydro chemical study of Mosul Governorate /Iraq. From the results, the errors in the estimated value are critical for the log variance. These results show that ordinary lognormal kriging is more effect than ordinary kriging technique under outlier.